2005
DOI: 10.1093/bja/aei236
|View full text |Cite
|
Sign up to set email alerts
|

Landmarks of the sacral hiatus for caudal epidural block: an anatomical study

Abstract: The triangle formed between the apex of the sacral hiatus and the superolateral sacral crests was found to have the features of an equilateral triangle. The sacrum and sacral hiatus are variable anatomical structures. However, the equilateral triangle located between the apex of the sacral hiatus and superolateral sacral crests will certainly be of use in determining the location of the sacral hiatus during CEB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
4
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 9 publications
4
100
4
8
Order By: Relevance
“…The data obtained in our study was in accordance to the study of Phalgun and Baskaran 6 who conducted their study on the sacra of Southern origin suggesting that the sacra of South Indians is quite similar to that of North Indians. On the contrary, the present study was not consistent with the studies of Senoglu et al and Bhattacharya et al 7,8 Regional and ethnic variation could be a possible explanation for this difference (Table 3). Phalgun and Baskaran, 6 Senoglu et al 7 and Bhattacharya et al 8 found the mean distance between the right and left lateral sacral crest and the apex of SH to be greater in their studies as compared to the data obtained in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…The data obtained in our study was in accordance to the study of Phalgun and Baskaran 6 who conducted their study on the sacra of Southern origin suggesting that the sacra of South Indians is quite similar to that of North Indians. On the contrary, the present study was not consistent with the studies of Senoglu et al and Bhattacharya et al 7,8 Regional and ethnic variation could be a possible explanation for this difference (Table 3). Phalgun and Baskaran, 6 Senoglu et al 7 and Bhattacharya et al 8 found the mean distance between the right and left lateral sacral crest and the apex of SH to be greater in their studies as compared to the data obtained in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…In Senoglu's study [8] of 96 dry sacral bones eight had abnormalities of the sacral hiatus (2 with posterior closure defect and six with agensis of the sacral hiatus).…”
Section: Discussionmentioning
confidence: 99%
“…Study by Dipali Rani Pal [8] et al observed that the distance between S2 and apex of sacral hiatus was 31.33 mm on an average (range 5 -60 mm) and the distance to the base of sacral hiatus was 54.88 mm (range 37 -39 mm). Study done by Senoglu N [12] et al stated that the distance between S2 foramen and apex of sacral hiatus was 35.37 mm on an average (range 11-62 mm) and the distance to the base of the sacral hiatus was 65.25 mm (range 39-85 mm). The distance between S2 foramen and apex of Sacral hiatus was 34.6 mm on an average (range 6 -52 mm ) and the distance to the base of the Sacral hiatus was 51.2 mm (range 15 -58 mm) was observed in our study which was similar to the previous studies.…”
Section: Median Distance In Millimetrementioning
confidence: 99%